Anesthesia-Related Risk Factors and Health Outcomes of Postoperative Urinary Retention in Appendectomy Patients - Mutar, Sabeeh Hussein Salih; Al-Darkazali, Ahmed Muwafaq Younus; Abdulkafi, Ali Qais (American Journal of Bioscience and Clinical Integrity, 2026)
Background: postoperative urinary retention (POUR) can delay recovery after appendectomy and may increase catheter-related complications. This study evaluated anesthesia-related factors and early urinary outcomes in appendectomy patients. Methods: a study of 100 appendectomy patients was analyzed. Variables included anesthesia type, surgical approach, catheter use, time to first void, and POUR status. Association between POUR and categorical variable were tested using Chi-square and Fisher’s exact tests as appropriate. Time to first avoid was compared between anesthesia group using Student’s t-tests with Mann-Witney U as sensitivity analysis, binomial logistic regression assessed anesthesia type and surgical approach as predictors of POUR. Results: POUR occurred in 7/100 (7.0%) patients. General anesthesia was used in 84% and spinal anesthesia was used in 16%: surgery was laparoscopic in 82% and open in 18%. POUR rates were 6.0% (5/84) under general anesthesia and 12.5% (2/16) under spinal anesthesia, with no significant association (χ² p=0.347: Fisher p=0.311). POUR occurred in 8.5% (7/82) of laparoscopic cases and 0% (0/18) od open cases (χ² p= 0.995: Fisher p=0.345). time to first void did not differ significantly between anesthesia groups (t (98) = -1.04, p=0.302: Mann-Whitney U p=0.449). logistic regression showed no significant predictors (Spinal vs General: β=0.742, p=0.407: open vs laparoscopic β= -17.137, p=0.995: AIC=53.2: McFadden R²= 0.069), with spare data instability due to zero POUR events in open group. Conclusion: POUR incidence was 7% with no statistically significant association with anesthesia type or surgical approach. Larger prospective studies with standardized definitions are warranted.